Pengaruh Harga, Promosi, Dan Lokasi Terhadap Kepuasan Konsumen Melalui Keputusan Pembelian Sebagai Variabel Intervening Pada Js Tea Cabang Panti Jember - Siti Fatimah; Hamzah Fansuri Jusuf; Nely Supeni (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study, entitled "The Effect of Price, Promotion, and Location on Consumer Satisfaction Through Purchase Decisions as Intervening Variables at JS Tea, Panti Jember Branch," aims to determine the direct and indirect effects of price, promotion, and location on consumer satisfaction and their influence on purchasing decisions as intervening variables. The population in this study was 50 respondents. The research method used was quantitative research. The sampling technique used was purposive sampling. The data analysis method used was path analysis with SPSS 25. The tests used were instrument testing (validity and reliability tests), classical assumption tests (normality test, heteroscedasticity test, multicollinearity test), hypothesis testing (t-test), and Sobel test. The results of the analysis indicate that promotion has no effect on purchasing decisions, price and location do. Furthermore, promotion and location do not affect customer satisfaction, price does affect customer satisfaction, and purchase decisions do not affect customer satisfaction. Furthermore, price, promotion, and location do not affect consumer satisfaction through purchasing decisions.